THE IMPORTANCE OF PROVERBS AND SAYINGS IN FULFILLING COMMUNICATIVE FUNCTIONS - Yadgorova Shohista Sobir kizi; PhD. Tadjiyeva Mastura Fayzullayevna (Western European Studies, 2025)
This article explores the communicative functions of proverbs and sayings, emphasizing their role in enhancing speech, ensuring clarity, reinforcing cultural identity, and conveying moral lessons. Proverbs serve as tools for effective communication, persuasion, and education, making them an integral part of both daily conversations and literary expressions. The study highlights their significance in preserving traditional wisdom and strengthening interpersonal relationships.
Keywords: Proverbs; sayings; communication; language